Non-professional Subtitling in Italy: the Challenges of Translating Humour and Taboo Language - Magazzù, Giulia (Hikma, 2018)
Fansubbing is one of the most common forms of non-professional audiovisual translation today, whose popularity is increasing thanks to digital technology advances. This happens especially in countries like Italy, where English is not the official language. The fansubbing phenomenon is at the same time a source of entertainment and knowledge, and it gives the possibility to fans to watch their favourite programme in their language. Despite being an illegal activity, the phenomenon has several benefits both for the programme itself and for the audience. Through the analysis of the amateur translation of the subtitles of an episode of Vicious, this paper will attempt to show the main translational differences between mainstream subtitling and fansubbing, focusing on the rendering of humour and taboo language.